The Institutional Framing of Policy Debates: Economics vs. Environment - Ventresca, M; Hoffman, A (1999)
By framing the economics versus environment debate as a mixed-motive situation, opportunities become visible that allow greater benefits to all interests in the debate. Yet, social, cultural, and institutional arrangements frame how these interests see these opportunities, creating a barrier to mixed-motive analyses. In this article, the authors use an institutional perspective to analyze how the economics versus environment debate emerges from institutions as presently structured. They present an analysis of its present framing based on three aspects of institutions-regulative, normative, and cognitive-and consider the prescriptive implications they expose at the managerial and organizational level of action. The authors conclude with an analysis of possible solutions to overcome them.